DETERMINANTS OF ASSET MISAPPROPRIATION BY EMPLOYEE FROM NEW FRAUD TRIANGLE THEORY PERSPECTIVE (Case Study on Holding Company in Central Java) - Yunita Lisnaningtyas Utami; Alfita Rakhmayani; Dwi Okto Imtichana; Neli Hajar (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
This study aims to analyze the factors affecting assets misappropriation from new fraud triangle theory perspective. This new perspective has four components that trigger fraud, namely: pressure, opportunity, capability, and integrity. In this study pressure factor is separated between financial and non-financial. This study’s population was all holding company employee, totaling 350 employees. The sampling technique employed was purposive sampling. Respondents of this study are employee that member of a holding company in Central Java. Employees chosen as samples are employees who have the authority to carry out certain tasks or positions, and the number of samples is proportional to each company. The data were obtained by distributing questionnaires to 88 employees. The data analysis then utilized Wrap PLS analysis tool version 6.0 software. The results of this study indicate that financial pressures, opportunities, and capabilities influence assets misappropriation. Meanwhile, non-financial pressure and integrity do not affect the misappropriation of assets.